Straight edge: uma genealogia das condutas na encruzilhada do punk - Fernandes, Walisson Pereira (2015)
Straight edge is the word used to describe persons who, in their everyday lives, are allied to the punk to not use substances considered addictive as alcohol, tobacco and psychoactive. Its beginnings derive from the late 1970s and early 1980s in the United States. However, the genealogical analysis of their practices through the centuries, going back to abstainers movements of the United States and England between the nineteenth and twentieth centuries and its ballast in the formation of moral, instilling in policy that determine behavior. With the emergence of punk in the 1970s as criticism of moralism, society and the state, the straight edge emerges in this context bringing a punk hygiene and, over the years, has become more violent and reductionist, emancipating itself from protoform and pouring a new ways to build and to solidify. The straight edge approached the environmental movements, looking to list anarchist aspects in their practice, but only reiterated other political forms that are linked more to progressivism that, in fact, to anarchism. In this purpose, several straight edgers who sought anarchism as a way of life, broke with the straight edge to proceed their libertarian path, and kept at the same time, the practical abstainers without the use of the nomenclature that identified previously. In Brazil, similar to what happened in the United States and Europe, the intensification of the straight edge scene brought also the anarchist cells of eruption for the construction of a group of vegan orientation appropriating an anarchist nomenclature for its consolidation among young libertarians causing not only the bedlam among their peers, but catches of anarchism and punk